2008
DOI: 10.1152/ajpgi.90217.2008
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing form and function in organotypic slices of the adult mouse parotid gland

Abstract: An organotypic slice preparation of the adult mouse parotid salivary gland amenable to a variety of optical assessments of fluid and protein secretion dynamics is described. The semi-intact preparation rendered without the use of enzymatic treatment permitted live-cell imaging and multiphoton analysis of cellular and supracellular signals. Toward this end we demonstrated that the parotid slice is a significant addition to the repertoire of tools available to investigators to probe exocrine structure and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Specifically, here we have investigated the exocytosis of large SCGs in SGs in vivo, showing that this process is regulated in a different fashion than what was previously reported in ex vivo systems and revealing aspects that were not previously appreciated (9)(10)(11)24). First, we have found that the β-adrenergic and not the muscarinic receptors elicit the fusion of the SCGs with the APM and that this process occurs in SGs in vivo through single fusion events and not through compound exocytosis (4,11). The reason(s) for the discrepancy between the data derived from explanted organs or acinar preparations and the animal model are difficult to determine.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Specifically, here we have investigated the exocytosis of large SCGs in SGs in vivo, showing that this process is regulated in a different fashion than what was previously reported in ex vivo systems and revealing aspects that were not previously appreciated (9)(10)(11)24). First, we have found that the β-adrenergic and not the muscarinic receptors elicit the fusion of the SCGs with the APM and that this process occurs in SGs in vivo through single fusion events and not through compound exocytosis (4,11). The reason(s) for the discrepancy between the data derived from explanted organs or acinar preparations and the animal model are difficult to determine.…”
Section: Discussionmentioning
confidence: 85%
“…Because there are conflicting data generated in in vitro and ex vivo systems about the role of β-adrenergic and muscarinic receptors in SGs, we sought to determine which stimulus elicits exocytosis of the SCGs in vivo. Exocytosis was assayed by estimating the reduction in the number of large SCGs after agonist stimulation, as shown by others (8,11). To this aim, we injected isoproterenol (Iso, a β-adrenergic agonist) and imaged the SCGs by time-lapse confocal microscopy ( Fig.…”
Section: Regulation Of Fusion Of Secretory Granules In the Salivary Gmentioning
confidence: 99%
See 3 more Smart Citations